Business Management Assistance For Small Micro Enterprises (Msmes), And Entrepreneurial Strategies In The Barangay San Isidro Area, Rodriquez Rizal Philippines - siti Mujanah; Sumiati Sumiati; Ruben M. Nayve, Jr; Anthony Mark Pejegria (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2023)
This International Community service aims to conduct service activities for lecturers in collaboration with international parties. In this case, the Faculty of Economics and Business, University of 17 August 1945 Surabaya, collaborates with the College of Business Administration Adamson University Manila, Philippines. This activity conducted business management assistance, product/service marketing strategies, managing finances for small micro enterprises (MSMEs), and entrepreneurial strategies in the Barangay San Isidro area, Rodriquez Rizal Philippines. MSMEs in this area had effortless management, which applied no business management, even though the business competition is tight here. Given the importance of this, Adamson University Manila Philippines took the initiative to provide assistance and training on business management in collaboration with lecturers from the University of 17 August 1945 Surabaya. Assistance and training activities were carried out for 16 hours on May 11 and 13, 2023. After the activities were carried out, the participants were very enthusiastic. They tried hard to manage the business by implementing proper management and marketing strategies, such as presenting their products well and offering goods to customers. Some have even dared to provide delivery services so that their turnover has increased and the business becomes more successful.